Asymptomatic atherosclerosis pathophysiology, detection, and treatment - Naghavi, Morteza (Contemporary cardiology, 2010)
Despite recent advances in the diagnosis and treatment of symptomatic atherosclerosis, available traditional screening methods for early detection and treatment of asymptomatic coronary artery disease are grossly insufficient and fail to identify the majority of victims prior to the onset of a life-threatening event. In Asymptomatic Atherosclerosis: Pathophysiology, Detection and Treatment, Dr. Morteza Naghavi and leading authorities from the Society for Heart Attack Prevention and Eradication (SHAPE) present a new paradigm for the screening and primary prevention of asymptomatic atherosclerosis.The text focuses on accurate, yet underutilized, measures of subclinical atherosclerosis, notably coronary artery calcium scanning and carotid intima-media thickness measurement. The authors introduce a comprehensive approach to identifying the vulnerable patients (asymptomatic individuals at risk of a near future adverse event). Additional chapters discuss future directions towards containing the epidemic of atherosclerotic cardiovascular disease using innovative solutions such as preemptive interventional therapies (bioabsorbable stents) for stabilization of vulnerable atherosclerotic plaques, mass unconditional Polypill therapy for population-based risk reduction, and ultimately vaccination strategies to prevent the development of atherosclerosis. Up-to-date and authoritative, Asymptomatic Atherosclerosis: Pathophysiology, Detection, and Treatment is a must-have for any cardiologist or primary care physician who wishes to practice modern preventive cardiology and manage the increasing number of asymptomatic atherosclerotic patients.